Immune profile focusing on B-cell activating factor in B-cell malignancies - Tagami, Nami; Yamagishi, Junya; Fujii, Wataru; Sanjoba, Chizu; Goto, Yasuyuki (Frontiers in Hematology, 2025)
BackgroundB-cell activating factor (BAFF) is crucial for B-cell survival, proliferation, and immunoglobulin secretion. However, its role in hematopoietic malignancies, particularly concerning B-cell differentiation stages, remains unclear. This study explored the involvement of BAFF in B-cell malignancy progression and treatment response.MethodsMouse malignant B-cell lineage cell lines A20 and MPC-11 OUAr cells were analyzed for responsiveness to BAFF both in vitro and in vivo. For an in vitro study, recombinant BAFF was examined for its capacities, rescuing those cells under drug-induced cytotoxicity. For an in vivo study, tumor progression induced by inoculation of the tumor cells was compared between wild-type and BAFF-knockout (BAFF-KO) mice. Transcriptomic analysis was conducted to assess immune responses and signaling pathways associated with BAFF-dependent tumor growth.ResultsMPC-11 OUAr cells exhibited characteristics of more differentiated B cells, with a capacity for IgG secretion and elevated expression of B-cell maturation antigen (BCMA). In vitro, recombinant BAFF reduced drug-induced cytotoxicity on A20 cells but had no apparent effect on MPC-11 OUAr cells. In vivo, BAFF-KO mice exhibited better survival when administered with MPC-11 OUAr cells than wild-type mice, whereas the opposite trend was observed when these mice were administered with A20 cells. Transcriptomic analyses revealed that wild-type mice bearing MPC-11 OUAr tumors exhibited elevated expression of genes linked to angiogenesis and the PI3K-Akt signaling pathway.ConclusionsOur findings suggest variable impacts of BAFF on B-cell lineage malignant cells depending on their cell types and highlight the complex role of BAFF in hematopoietic malignancies. Even when BAFF serves as a promoter of B-cell lineage tumors, its roles may not be restricted to its direct effects on malignant cells but may involve indirect effects on other cells constituting the tumor microenvironment, leading to an environment favorable to the malignant cells. The differential impact of BAFF on lymphoma subtypes underscores the need for targeted therapeutic strategies modulating BAFF signaling in B-cell malignancy.